First description of the male of the spider Tibellus paraguensis Simon, 1897 (Araneae: Philodromidae), with new distribution records - Achitte-Schmutzler, Helga C.; Rubio, Gonzalo D. (Zootaxa, 2016)
The genus Tibellus Simon, 1875 currently includes 51 species (WSC 2016); it presents some taxonomic difficulties, due to morphological variability, and similarities among some congeners (Efimik 1999). Studies on the genus were undertaken by Gertsch (1933) and Schick (1965) from America, Tikader (1980) from India, Van den Berg & Dippenaar-Schoeman (1994) from the Afrotropical region, and Efimik (1999) from the East Palearctic region.